C17 prevents inflammatory arthritis and associated joint destruction in mice. - Connie Chao (Public Library of Science (PLoS), 2011)
C17 was first described about ten years ago as a gene expressed in CD34+ cells. A more recent study has suggested a role for C17 in chondrogenesis and development of cartilage. However, based on sequence analysis, we believe that C17 has homology to IL-2 and hence we present the hypothesis that C17 is a cytokine possessing immune-regulatory properties. We provide evidence that C17 is a secreted protein preferentially expressed in chondrocytes, hence in cartilage-rich tissues. Systemic expression of C17 in vivo reduces disease in a collagen antibody-induced arthritis model in mice (CAIA). Joint protection is evident by delayed disease onset, minimal edema, bone protection and absence of diverse histological features of disease. Expression of genes typically associated with acute joint inflammation and erosion of cartilage or bone is blunted in the presence of C17. Consistent with the observed reduction in bone erosion, we demonstrate reduced levels of RANKL in the paws and sera of mice over-expressing C17. Administration of C17 at the peak of disease, however, had no effect on disease progression, indicating that C17's immune-regulatory activity must be most prominent prior to or at the onset of severe joint inflammation. Based on this data we propose C17 as a cytokine that s contributes to immune homeostasis systemically or in a tissue-specific manner in the joint.